USING PLANETSCOPE DATA TO ESTIMATE CARBON SEQUESTRATION OF MANGROVE FORESTS: A CASE STUDY IN TIEN YEN DISTRICT, QUANG NINH PROVINCE - Hai Hoa, Nguyen; Tri Son, Ha; Thi Linh, Nghiem; Ojeda de Vicent, Daniel; Ngoc Linh, Nguyen (Journal of Forestry Science and Technology, 2023)
Mangrove forests, typically found along tropical and subtropical coastlines, have a crucial role in preventing coastal erosion, mitigating the effects of wave actions, and safeguarding coastal habitats. This study utilized PlanetScope mangrove forests and a Combined Mangrove Recognition Index (CMRI), which was suitable for detecting mangrove cover along the coast of Tien Yen district with an overall accuracy of over 93.0% and a Kappa coefficient greater than 0.90 for the selected years. The total area of coastal mangrove forests along the coast of Tien Yen, Quang Ninh province has increased by 137.7 ha in 2023 compared to 2020. The total AGB and AGC of mangrove forests were estimated at 241,730,970 tons and 114,822,211 tons in 2023, respectively. The total CO2 sequestration was estimated at 421,397,514 tons in 2023, which represents a decrease of 17,813,872.1 tons compared to 2020. The study highly suggests the adoption of blue carbon approach for sustainable mangrove management in Tien Yen district, including Payment for Ecosystem Services (PES) schemes. However, certain key factors, such as increasing awareness of the value of the mangrove ecosystem, promoting the involvement of local communities, and revising policy issues related to PES, need to be addressed to ensure the success of the mangrove blue carbon option in Tien Yen district.